EVALUATING THE QUALITY OF GREEN OPEN SPACES IN ADO-EKITI, EKITI STATE. NIGERIA - Adedeji Afolabi Idowu & Olowookere Clement Adebayo (International Journal of Research Science and Management, 2019)
The essentials of urban open space management recommend that a mindfully implemented urban improvement should incorporate more than just great buildings. It ought to incorporate parks and open spaces on the ground that both buildings and open spaces benefit from each other through the quality of each space. Furthermore, it provides benefits from the economical, social, communal, environmental and aesthetical aspects.Parks and open spaces improved the personal satisfaction of urban communities and neighborhood by the city enhancements and facilities. The reasonable system on nature of a neighborhood park in this paper is gotten from a multidisciplinary study in the fields of landscaping design, relaxation, amusement, tourism industry and the environment. This system takes into consideration theory based combination of certainties and thoughts as well as functional ramifications for the advancement of tools to assess the aspects of value in Ado Ekiti Neighborhood Park. Neighborhood Park as the subject of evaluation for this tool since it has social, monetary and social qualities on our everyday lives. In addition to the fact that it provides income benefits for health and mental prosperity, it also serves as a societal and community gathering place for certain residential neighborhood. This paper fundamentally evaluates the result of investigations literature that characterizes the idea of quality for a neighborhood park. The outcome of this study would be utilized to control future development of a structure to characterize parts of value in Ado-Ekiti neighborhood parks.